Health behaviors and psychological health control types among university students - Sak, Jarosław; Wiechetek, Michał; Jarosz, Marek; Pawlikowski, Jakub; Kapusta, Andrzej; Rejdak, Lidia; Książek, Piotr (Polish Journal of Public Health, 2013)
Introduction. The factors that influence gaining good results of prophylactic programs are human attitudes to health. These attitudes manifest themselves as individual beliefs and health-oriented behaviors.Aim. The aim of the research was to investigate relations between the health control types and health behaviors performed by the university students.Material and methods. The research was conducted in the group of 532 Polish university students in 2009. The average age in the researched group was M=20.74 (SD=1.542). Two questionnaires were used in the survey: the Multidimensional Health Locus of Control Scale (MHLC) worked out by Wallston, Wallston & R. DeVellis and the Inventory of Health Behaviors (IHB) by Juczynski. The MHLC scale allows for evaluating three dimensions of the health locus of control, namely: Internal Health Locus of Control (IHLC), Powerful Others Health Locus of Control (PHLC) and Chance Health Locus of Control (CHLC). The Inventory of Health Behaviors (IHB) allows for estimating various kinds of health behaviors categorized into four groups: diet habits, preventive behaviors, positive psychical attitude and health practices.Results. The health behaviors correlate most strongly with the PHLC dimension. The higher result in the PHLC dimension was obtained, the higher were the results in the following three dimensions: preventive behaviors, positive psychical attitudes and health practices.Conclusions. Students manifest the belief that internal control (IHLC) prevail over external sources of health control (PHLC, CHLC). In the studied group, the women have exhibited significantly greater intensification of good diet habits and preventive behaviors. The main factor modifying preventive behaviors performed by researched students is the belief in the influence of other people on the students’ health status